2022
DOI: 10.3390/ijerph191811778
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Burpee on Endurance and Short-Term Memory of Adolescents

Abstract: Aim—The purpose of this study was to assess the effect of the Burpee exercise on the endurance and short-term memory of adolescents aged 15–16 years. Methods—The experiment was performed in a coeducational school in Kirov (Russia). The four-month study involved 52 adolescents of both genders. During the study period, 30 physical education lessons were held in each class. Adolescents from the control group were involved in a typical program (also aimed at improving endurance), and adolescents from the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a study conducted with forty-five female and fifty-one male university students, it was found that parameters of body composition were significantly correlated with strength endurance in 18-29-year-old females and males, while parameters indicating obesity (BMI, BFM, and VFM) were negatively correlated, but least significantly, with motor performance (number of completed cycles) during excessive effort (Podstawski et al, 2019). In a study by Polevoy et al (2022) focusing on different age groups, they evaluated the effects of the Burpee exercise on endurance and short-term memory in 15-16-year-old adolescents. They found a significant improvement in variables like endurance and cognitive abilities, such as memory, when physical exercise with Burpees was performed in every Physical Education class for adolescents aged 15-16 years.…”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted with forty-five female and fifty-one male university students, it was found that parameters of body composition were significantly correlated with strength endurance in 18-29-year-old females and males, while parameters indicating obesity (BMI, BFM, and VFM) were negatively correlated, but least significantly, with motor performance (number of completed cycles) during excessive effort (Podstawski et al, 2019). In a study by Polevoy et al (2022) focusing on different age groups, they evaluated the effects of the Burpee exercise on endurance and short-term memory in 15-16-year-old adolescents. They found a significant improvement in variables like endurance and cognitive abilities, such as memory, when physical exercise with Burpees was performed in every Physical Education class for adolescents aged 15-16 years.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, exercises that can develop leg muscle strength are (burpees), and burpees are exercises that utilize muscle groups throughout the body (Yohei Yamashita, 2023). Burpee exercises require the body to lift and push body weights (Georgiy et al, 2022). Based on the power training that has been described, one of the important factors in the process of mastering volleyball, especially smash, is the strength of leg muscles, arm muscles and technique (Amalia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%